Estudio sobre las motivaciones de deserción estudiantil en la Universidad Industrial de Santander - Zárate-Rueda, Ruth; Marcela Socha, Claudia (Prospectiva. Revista de Trabajo Social e Intervención Social, 2009)
The present articulates it condenses an investigation that had aimed to interpret the meanings attributed by the students of UIS to experience college dropout during the years 2003 to 2006, taking into account the personal influences, socio-economic, cultural, academic and institutional, that motivate this phenomenon.The research provides results that allow us to identify and evaluate reason and meanings of students to change the dynamics in the work of human development and teaching of the University, providing premises and categories of analysis to facilitate the creation of spaces and building strategies to prevent and/ or decrease in the drop at UIS.Among the major findings is that the reason of greater personal impact on the phenomenon of desertion are the behaviors, feelings and characteristics of the student at the lack of 3academic guidance and poor training in the level socio- economic precariousness of their families, the difficulty to sustain in the University- wide assessment of institutional policies , policies on resource assessment, methods and methodologies of the State University or in general culture level: a cultural identity with low expectations for higher education.In general, the investigation established that the issues raised in the conceptual and theoretical framework as well as those contributed by the background research regarding the motivations of desertion are: personal, socio- economic, cultural, academic and institutional, are valid and are configured as such the classrooms of the Industrial University of Santander, UIS.